Evaluation of efficacy and safety of long-term use of amtolmetin guacil in rheumatic diseases: results of a 9-month observational AURORA study (Amtolmetin guacil: allRussian Register for Osteoarthritis, Rheumatoid arthritis and Ankylosing spondylitis) - A. E. Karateev; E. L. Nasonov; S. I. Glukhova; A. A. Barakat; R. L. Gibadullina; E. A. Ageeva; O. S. Fedorova; T. S. Timofeeva; G. R. Mikhailova; A. E. Nasonova (Научно-практическая ревматология, 2019)
Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for the treatment of rheumatic diseases (RD). In some cases, their long-term use is advisable: NSAIDs slow the progression of spondylarthritis, are an important element in the control of chronic pain in osteoarthritis (OA) and rheumatoid arthritis (RA). However, the risk of serious adverse events (AE) should be considered. A good choice for long-term therapy may be amtolmetin guacil (AMG), which rarely induce gastrointestinal AE. The aim of the study was to assess the effect and safety of long-term use of AMG in RD. Material and methods. An open observational study was conducted in which AMG (Nayzilat) was assigned to 442 patients with OA (mean age 60.6±10.2 years, women 88.7%), 126 patients with RA (55.0±14.0 years, women 84.2%) and 73 with ankylosing spondylitis (AS, 47.0±12.0 years, women 30.0%). The dose of AMG depended on the clinical situation and was determined by the attending physician: from 1800 to 600 mg/day. The main criterion of the effect was the changes of pain by numeric rating scale (NRS), additional measures of efficacy were pain on the WOMAC and HAQ for OA, DAS28 for RA, BASDAI, BASFI and ASDAS-CRP for AS. The result of treatment was evaluated during three consecutive visits every 3 months (9 months of follow-up). Results and discussion. At the end of follow-up 65.2% of patients with OA, 75.3% of patients with RA and 82.2% of patients with AS continued treatment with AMG. The reasons for discontinuation of treatment were significant reduction or absence of pain (70.3%), the patient's decision (26.6%) or AE (3.1%). At the end of follow-up, there was a significant decrease in pain intensity compared to the baseline: in OA, the median pain decreased from 5.6 [4.1; 6.9] to 3.4 [1.7; 5.1], in RA from 5.8 [4.0; 7.5] to 3.4 [2.0; 4.8], in AS from 5.8 [4.2; 7.5] to 3.1 [1.5; 5.0] according to NRS, the difference was significant in all groups (p<0.001). In OA, the median WOMAC pain decreased from 127 [24; 159] to 13.7 [14; 40] (p<0.001), the average HAQ value – from 0.54±0.44 to 0.34±0.26 (p<0.001). In RA, the average value of DAS28 decreased from 4.81±1.18 to 4.30±1.24 (p<0.05). The number of painful and swollen joints, ESR and C-reactive protein also significantly decreased. In AS, the median BASDAI index decreased from 4.5 [1.0; 8.0] to 3.0 [0; 8.0] (p<0.001). The number of patients with high activity according to ASDAS-CRP (>3.5) decreased from 76.9 to 25.8% (p<0.001). The BASFI index did not changed. 77.9% of patients with OA, 77.0% with RA and 74.5% with AS were satisfied with the results of AMG treatment. AMG tolerance was good. Mild dyspepsia was observed in 15–25% of patients. AE, which caused the discontinuation of therapy, were observed only in 6 (0.93%) patients. There was no development or deterioration of hypertension, as well as other cardiovascular complications. Conclusion. AMG is an effective NSAID with good tolerability, which is advisable to use for long-term treatment of RD. Limitations are the open nature of the study and the absence of a control group.